Roles of dental pulp fibroblasts in the recognition of bacterium-related factors and subsequent development of pulpitis - Tadashi Nakanishi; Daisuke Takegawa; Kouji Hirao; Kanako Takahashi; Hiromichi Yumoto; Takashi Matsuo (Elsevier, 2011)
As caries-related bacteria invade deeply into dentin and come into close proximity to the pulp, inflammatory cells (such as lymphocytes, macrophages and neutrophils) infiltrate into the bacterium-invaded area and consequently pulpitis develops. Many types of cytokines and adhesion molecules are responsible for the initiation and progression of pulpitis. Dental pulp fibroblasts, a major cell type in the dental pulp, also have capacity to produce pro-inflammatory cytokines and express adhesion molecules in response to pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide. The innate immune system senses microbial infection using pattern recognition receptors, such as Toll-like receptors (TLRs) and nucleotide-binding oligomerization domain (NOD), for PAMPs. In this review, we summarize the roles of dental pulp fibroblasts in the recognition of invaded bacterium-related factors via TLR and NOD pathways, and the subsequent pulpal immune responses, leading to progressive pulpitis.